Mode of progression in smoldering multiple myeloma: a study of 406 patients - Nadine H. Abdallah; Arjun Lakshman; Shaji K. Kumar; Joselle Cook; Moritz Binder; Prashant Kapoor; Angela Dispenzieri; Morie A. Gertz; Martha Q. Lacy; Suzanne R. Hayman; Francis K. Buadi; David Dingli; et al. (Blood Cancer Journal, 2024)
Abstract The approach to patients with high-risk smoldering multiple myeloma (SMM) varies among clinicians; while some advocate early intervention, others reserve treatment at progression to multiple myeloma (MM). We aimed to describe the myeloma-defining events (MDEs) and clinical presentations leading to MM diagnosis among SMM patients seen at our institution. We included 406 patients diagnosed with SMM between 2013–2022, seen at Mayo Clinic, Rochester, MN. The 2018 Mayo 20/2/20 criteria were used for risk stratification. Median follow-up was 3.9 years. Among high-risk patients who did not receive treatment in the SMM phase (n = 71), 51 progressed by last follow-up; the MDEs included: bone lesions (37%), anemia (35%), hypercalcemia (8%), and renal failure (6%); 24% met MM criteria based on marrow plasmacytosis (≥60%) and/or free light chain ratio (>100); 45% had clinically significant MDEs (hypercalcemia, renal insufficiency, and/or bone lesions). MM diagnosis was made based on surveillance labs/imaging(45%), testing obtained due to provider suspicion for progression (14%), bone pain (20%), and hospitalization/ED presentations due to MM complications/symptoms (4%). The presentation was undocumented in 14%. A high proportion (45%) of patients with high-risk SMM on active surveillance develop end-organ damage at progression. About a quarter of patients who progress to MM are not diagnosed based on routine interval surveillance testing.